PENGARUH JOB DESCRIPTION DAN DISIPLIN TERHADAP KINERJA KARYAWAN PT KINCO PRIMA - Binton, Binton; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2021)
Companies are currently increasingly competitive competition, this study aims to examine the extent to which the role of job descriptions, discipline and leadership in improving employee performance. The sampling technique was saturated sampling, namely by taking the entire population of 107 respondents. The data technique was used by distributing questionnaires and literature study. The analytical method used is multiple regression which includes: validity test, reliability test, normality test, multicolin meaning test, heteroscedasticity test, determination test, partial test. The results showed that the job description partially affected 3.405> 1.983 from the t table, so 0.00 was smaller than alpha 0.05. Meanwhile, discipline partially affects 8,368> 1,983 of the t table. Together with the job description and has a significant effect. amounting to 106.188> 3.080 from the F table, then 0.00 is smaller than alpha 0.05. And the significance value of the simultaneous test. The results of the study on employee performance, performance, and R2 test showed an effect of 81.9% of the research results showed that Job Description and had a significant effect.